Warm Middle Miocene Indian Ocean Bottom Water Temperatures: Comparison of Clumped Isotope and Mg/Ca‐Based Estimates. Issue 11 (21st November 2020) - Modestou, S. E.; Leutert, T. J.; Fernandez, A.; Lear, C. H.; Meckler, A. N.
Abstract: The middle Miocene is an important analogue for potential future warm climates. However, few independent deep ocean temperature records exist, though these are important for climate model validation and estimates of changes in ice volume. Existing records, all based on the foraminiferal Mg/Ca proxy, suggest that bottom water temperatures were 5–8°C warmer than present. In order to improve confidence in these bottom water temperature reconstructions, we generated a new record using carbonate clumped isotopes (Δ47 ) and compared our results with Mg/Ca‐based estimates for the Indian Ocean at ODP Site 761. Our results indicate temperatures of 11.0 ± 1.7°C during the middle Miocene Climatic Optimum (MCO, 14.7–17 Ma) and 8.1 ± 1.9°C after the middle Miocene Climate Transition (MCT, 13.0–14.7 Ma), values 6 to 9°C warmer than present. Our record also indicates cooling across the MCT of 2.9 ± 2.5°C (uncertainties 95% confidence level). The Mg/Ca record derived from the same samples indicates temperatures well within uncertainty of Δ47 . As the two proxies are affected by different non‐thermal biases, the good agreement provides confidence in these reconstructed temperatures. Our Δ47 temperature record implies a 0.6‰ seawater δ 18 O change over the MCT, in good agreement with previously published values from other sites. Our data furthermore confirm overall high seawater δ 18 O values across the middle Miocene, at face value suggesting ice volumes exceeding present‐day despite the warm bottom water temperatures. This finding suggests previously underappreciated additional influences on seawater δ 18 O and/or a decoupling of ice volume and ocean temperature. Plain Language Summary: In the context of understanding global warming, the middle Miocene (approximately 12 to 18 million years ago) is an important time in Earth's geological history because atmospheric carbon dioxide levels in parts of this time period were comparable to those predicted for the near future. An accurate understanding of the temperature of deep ocean water in the past is an important constraint for climate studies because that information is needed in order to understand important processes such as ocean heat transport and sea level changes. In this study, we compared the only two temperature proxies available for ancient bottom water, the Mg/Ca and carbonate clumped isotope paleothermometers, to help understand their accuracy in estimating temperatures from the middle Miocene period. We found that the two proxies agree well at our study site (Ocean Drilling Program Site 761 in the Eastern Indian Ocean) despite unresolved issues with both proxies, suggesting that the warm temperatures reconstructed are realistic (approximately 11°C between 15 and 17 Ma, and about 8°C between 11.5 and 13 Ma, compared to approximately 2°C today). Key Points: Benthic foraminiferal clumped isotope and Mg/Ca temperature proxies are compared in the context of middle Miocene climate change Results of the two proxies agree well at ODP Site 761, exhibiting relatively warm bottom water temperatures up to 9°C warmer than today The warm temperatures lead to reconstruction of relatively heavy seawater δ 18 O compared to modern, especially after 13 Ma